Learning and memory profiles in youth with perinatal stroke: a study of the Child and Adolescent Memory Profile (ChAMP). Issue 1 (2nd January 2022) - Virani, Shane; Rasmussen, Carmen; Zivanovic, Nikola; Smithson, Lisa; Pei, Jacqueline; Andersen, John; Yager, Jerome Y.; Kirton, Adam; Brooks, Brian L.
ABSTRACT: There is limited understanding of the effect of perinatal stroke on child and adolescent learning and memory abilities. This study sought to evaluate the clinical utility of the Child and Adolescent Memory Profile (ChAMP) in quantifying memory performance in youth with perinatal stroke. Children and adolescents aged 6–16 years old with a history of perinatal stroke (PS; n = 41) completed two subtests from the ChAMP (Lists and Objects). Age, sex, and ethnicity-matched healthy control (HC) data were obtained from the test publisher's standardization data set. Participants with a history of PS performed significantly worse (p < .05) with medium effect size ( ƞp 2 ≥ .06) than HC on the ChAMP Screening Index and on all ChAMP Lists and Objects scaled scores. Classification accuracy for the ChAMP scores ranged from 57% to 68% with the area under the curve ranging from .62-.75. No significant group differences on ChAMP performance (p > .05) were found for stroke side (left versus right-sided) or for seizure history (present versus absent). This study supports the utility of the ChAMP in perinatal stroke patients by demonstrating significantly worse performance in verbal and visual memory than HC. Classification accuracy is limited, but supportive for the Screening Index and Objects Delayed scores. The ChAMP may be a useful tool for evaluating cognition in this population when taken alongside the context of other tests, background history, and clinical observations.